1990
DOI: 10.1002/chin.199008194
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Cleavage Reactions of Benzothiazepinylchromone Derivatives.

Abstract: The thiazepines (III) and (V) are prepared by reaction of the unsaturated ketones (I) and (IV) with the amino thiol (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The reaction between 3-(2-acylvinyl)chromones and hydrazine in glacial acetic acid gives derivatives XXXVI containing pyrazoline ring [98], while the reaction of similar ehromones with o-aminothiophenol and subsequent intramolecular cyclocondensation gives products XXXVII containing benzothioazepine residue [99]. In the same study [104] was also found that reaction of nitrilimines XLV with substituted acetylenes and ethylenes gives pyrazolylchromones XLVI and pyrazolinylchromones XLVII, respectively.…”
Section: Methods Of Synthesis Of 3-hetarylchromonesmentioning
confidence: 87%
“…The reaction between 3-(2-acylvinyl)chromones and hydrazine in glacial acetic acid gives derivatives XXXVI containing pyrazoline ring [98], while the reaction of similar ehromones with o-aminothiophenol and subsequent intramolecular cyclocondensation gives products XXXVII containing benzothioazepine residue [99]. In the same study [104] was also found that reaction of nitrilimines XLV with substituted acetylenes and ethylenes gives pyrazolylchromones XLVI and pyrazolinylchromones XLVII, respectively.…”
Section: Methods Of Synthesis Of 3-hetarylchromonesmentioning
confidence: 87%